Seminar Psychological Well-Being Peserta Didik dalam Proses Pembelajaran - NIrfayanti, Nirfayanti; Ernawati, Ernawati; Rahmawati, Rahmawati; Syamsuriyawati, Syamsuriyawati; Nasir, A. Muhajir; Rusdi, Hikmah; Riyanti, Rika; Lestari, Pertiwi Indah; Suryaningsih, Ita; Setiawan, Dedy (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muslim Maros, 2024)
The psychological well-being of students is very important to create a good and productive learning environment. In an effort to provide SMAS Hang Tuah Makassar teachers with a better understanding of the concept of mental health and strategies to improve it in the learning environment, a seminar on Psychological Well Being of Students in the learning process was held. Participants gain a broad understanding of the factors that influence students' psychological well-being, the role of teachers in creating a supportive environment, and methods and approaches that are useful for improving psychological well-being. The results of the pre- and post-test evaluations showed that the teachers understood and comprehended this concept better after attending the seminar.